In defence of newborns: a response to Kingma. Issue 8 (9th July 2021) - Colgrove, Nicholas
Abstract : Recently, I argued that subjects inside of artificial wombs—termed 'gestatelings' by Romanis—share the same legal and moral status as newborns (neonates). Gestatelings, on my view, are persons in both a legal and moral sense. Kingma challenges these claims. Specifically, Kingma argues that my previous argument is invalid, as it equivocates on the term 'newborn'. Kingma concludes that questions about the legal and moral status of gestatelings remain 'unanswered'. I am grateful to Kingma for raising potential concerns with the view I have presented. In this essay, however, I argue that (most) of Kingma's objections are unpersuasive. First, my original argument does not equivocate on terms like 'newborn' or 'neonate'. The terms denote human beings that have been born recently; that is what matters to the argument. Charges of equivocation, I suspect, rest on a confusion between the denotation and connotations of 'newborn' (or 'neonate'). Next, I show that, contra Kingma, it is clear that—under current law in the USA and UK—gestatelings would count as legal persons. Moral personhood is more difficult. On that subject, Kingma's criticisms have merit. In response, however, I show that my original claim—that gestatelings should count as moral persons—remains true on several (common) philosophical accounts of personhood. Regarding those accounts that imply gestatelings are not moral persons, I argue that advocates face a troubling dilemma. I conclude that regardless of which view of moral personhood one adopts, questions about the moral status of gestatelings are not 'unanswered'.